Universities and the challenge of implementing sustainability policies:: the experience of the Universidade do Estado de Minas Gerias in the municipality of Divinópolis - Nascimento, Alexandre Túlio Amaral; Machado, Úrsula Gisele Cordeiro; Casarin, Carine; Valadares, Tatiane Castaño; Silva, Gabriele Andreia da (Sustainability in Debate, 2016)
This study aims to enable the dialogue between the Divinópolis campus of Minas Gerais State University and the local society, in regard to public policies that are relevant to sustainability: Brazil’s Forest Code and its National Solid Waste Policy. Public documents and interviews were the methods employed to collect data on the perceptions of university researchers and members of civil society concerning these public policies. We present the current status of these policies and make pertinent recommendations about how university-based research can improve sustainability in the municipality of Divinópolis. This approach can be adapted to various research institutions and to the municipalities in which they operate. We also propose a reflection on the role of universities and public administration in setting sustainability paradigms in their communities.